Demystifying career paths after graduate school : a guide for second language professionals in higher education - Kubota, Ryuko; Sun, Yilin, 1953- (Emerald Publishing Limited : Information Age Pub., 2012)
This edited book offers concrete information and useful suggestions to graduate students who are seeking employment at institutions of higher education in North America and other parts of the world. This book also targets entry-level faculty members who are exploring increased participation in professional activities. The book features critical turning points in career trajectories, demystifies hidden institutional structures, and illuminates blind spots that are critical for career success.The authors are scholars from nonnative-English-speaking and/or racially minority backgrounds in the fields of applied linguistics and teaching English to speakers of other languages. The firsthand suggestions offered by these authors are also applicable to non-minority professionals and those in other related disciplines. Furthermore, the book assists faculty mentors and administrators to understand the unique challenges and issues faced by minority professionals.Distinctive features of the book are: (1) theme-based approach with concrete examples and specific advice; (2) focus on victory narratives of success and strategies rather than victim narratives of struggles; (3) accessible style, and (4) wide range of experiences narrated by both novice and established scholars. This guidebook can be read independently or adopted as a resource book for graduate seminars.
Keywords: English language -- Study and teaching -- Foreign speakers -- Vocational guidance.; English language -- Study and teaching -- Vocational guidance.; English teachers -- Employment.; English teachers -- Training of.; Language Arts & Disciplines -- General.; Higher education, tertiary education.; Language: reference and general.; elektronické knihy; electronic books